Isotopic polymorphism in pyridine. - Crawford, S; Kirchner, M; Bläser, D; Boese, R; David, W; Dawson, A; Gehrke, A; Ibberson, R; Marshall, W; Parsons, S; Yamamuro, O (2009)
Not so simple: It is normally assumed that deuteration has only a minor effect on the stabilities of crystal structures. This assumption is wrong for pyridine. A low-temperature polymorph exists for [D5]pyridine, but not for [H5]pyridine, which adds a further twist to the already unusual structural chemistry of one of the simplest and most familiar laboratory chemicals. (Figure Presented). © 2009 Wiley-VCH Verlag GmbH and Co. KGaA.